Review of Scabies: Current Update of Patogenesis, Transmission, and Elimination - Trasia, Reqgi First (Jurnal Ilmu Medis Indonesia, 2023)
Purpose: Scabies is a very common dermatological condition that accounts for a large proportion of skin diseases in developing countries. The disease spreads globally, with an estimated population of 200 million and a prevalence ranging from 0.2% to 71%. According to the Indonesian Ministry of Health, the prevalence of scabies in Indonesia has decreased from 5.60% to 12.96% in 2008 to 4.9% to 12.95% in 2009. This review will provide an overview of the pathogenesis, transmission, and elimination of scabies so that scabies cases in Indonesia can be controlled properly. Research Methodology: This article reviews 21 recent studies and discusses them comprehensively. Results: Scabies often does not receive attention because it is not life-threatening; however, the result is itching, which can cause discomfort in sufferers. The spread of scabies has been widespread. Discussion on the pathogenesis, transmission, and elimination of scabies from various regions in Indonesia is still not comprehensive. Limitations: Approximately 90% of scabies transmission is carried out by adult female mites, especially gravid ones. Mites cannot jump or fly, but move by creeping. The ability of mites to infest decreases with time, and mites are outside the host body. Contribution: First, increasing awareness of scabies and advocacy of potential funding parties’ eradication programmes. Second, clinical and epidemiological research should be conducted to better understand the effects of the disease. Third, we developed and implemented a strategy for effective scabies control.